Mode, Pattern and Precipitating factors of Acute Poisoning in a Southern District Hospital in Bangladesh (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Acute poisoning is common in Bangladesh and causes a significant number of hospital admissions. That causes a number of mortality, morbidity as well as increases the economic burden in health care system. But it can be prevented. For that it is necessary to observe and study the poisoning related factors and events around the country. So, the aim of our study is to find out and describe the mode, pattern and precipitating factors of poisoning in a southern district hospital. This cross-sectional observational study was done in the department of Medicine of Pirojpur District Hospital, from January to December 2020. The study was conducted among 100 patients of both genders those were hospitalized with the history of poisoning. In the study young people (40% in 14-25 years and 37% in 26-35 years) were predominantly affected and 61% were female. Suicidal attempt was the commonest (74;74%) mode of poisoning that mostly caused by pesticides. Stupefying mode was observed in case of 15(15%) male travelers as street poisoning. Highest number of poisoning (45;45%) was caused by pesticides. The sedative (14;14%), copper sulphate (11;11%) and harpic (5;5%) poisoning was observed mostly as a suicidal mode. History of savlon (4;4%) and Kerosene (2;2%) poisoning was found as an accidental mode. As a recreational mode two male were admitted with alcohol poisoning. Considering the precipitating factor, maximum cases (54;54%) had the history of unsatisfactory family events. Street poisoning (15;15%) was precipitated by the careless behavior of travelers. Accidental poisoning (9,9%) was invited by unmindful and hurried attitude. Problem related to love and affair was observed in 8(8%) cases. Study and examination result precipitated poisoning in 7(7%) cases. History of job and income dissatisfaction was found in 4(4%) cases. So those factors related with the poisoning should be considered. That will help to make a comprehensive strategy in order to resist these preventable events.Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):85-89